1990
DOI: 10.1007/bf00133893
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting staff's intentions to leave the university

Abstract: This article investigates factors related to the intention to leave the university job among Norwegian university staff. Its main conclusions are: among staff intending to leave their institution, colleagial relations (i.e. relations between colleagues) constituted the clearest reason to leave. General job satisfaction did also rather strongly predict intention to leave. The study showed that staff who found their work less intrinsically satisfying than others more often intended to leave their institution. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 3 publications
(3 reference statements)
1
24
0
2
Order By: Relevance
“…However, a definitive answer remains elusive as to how important salary is to faculty's turnover behavior. Some researchers (e.g., Pfeffer and Lawler 1980;Weiler 1985) argued that salary was a critical factor for turnover, but such notions encountered strong disagreement (Ambrose et al 2005;Barnes et al 1998;Manger and Eikeland 1990). Between these extremities, the study by Smart (1990) identified salary as an important consideration only for nontenured faculty, which was partly consistent with the findings of Ehrenberg et al (1990) that compensation appeared to be more of a concern for assistant and associate level faculty.…”
Section: Subjective Evaluation Of the Work Environmentmentioning
confidence: 53%
See 1 more Smart Citation
“…However, a definitive answer remains elusive as to how important salary is to faculty's turnover behavior. Some researchers (e.g., Pfeffer and Lawler 1980;Weiler 1985) argued that salary was a critical factor for turnover, but such notions encountered strong disagreement (Ambrose et al 2005;Barnes et al 1998;Manger and Eikeland 1990). Between these extremities, the study by Smart (1990) identified salary as an important consideration only for nontenured faculty, which was partly consistent with the findings of Ehrenberg et al (1990) that compensation appeared to be more of a concern for assistant and associate level faculty.…”
Section: Subjective Evaluation Of the Work Environmentmentioning
confidence: 53%
“…First, due to limitations of the data set, some potentially important variables were not included in the analyses, including academic reputation of an institution (Johnsrud and Heck 1994) and personal relationships with colleagues and administrators (Ambrose et al 2005;Barnes et al 1998;Manger and Eikeland 1990;Weiler 1985). Second, turnover intention was the outcome variable; although it is the best indicator of the actual turnover, they are different.…”
Section: Limitationsmentioning
confidence: 98%
“…Manger & Eikeland (1990) cites that job turnover research has focused on the relation between the intention to leave the organization and actual leaving. "Greater the complementarily, the effect on satisfaction and intentions to leave (turnover intentions) will be greater" (Shalley, Gilson, & Blum, 2000).…”
Section: Turnover Intentionsmentioning
confidence: 99%
“…Many anecdotal cases involving professors changing institutions quite often involve offers of greater research funding and/or less teaching workload. Other factors, such as job satisfaction, relationships between colleagues (Manger & Eikeland 1990), and cultural and lifestyle reasons, might also play a role in accepting a position in a particular university.…”
Section: Do Top-ranked Universities Pay Higher Salaries?mentioning
confidence: 99%